Preparation and in- vitro Evaluation of Bioadhesive Vaginal Film of Tinidazole - Thomas, Lena Murad; Al-Akkam, Entidhar J.; Daood, Noor Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2024)
Bioadhesive vaginal film is becoming a more effective and convenient dosage form compared to suppositories and gel for vaginal application as a method for the treatment of vaginal infections. This study aimed to prepare and characterize bioadhesive films of tinidazole to be used for vaginal delivery over a prolonged period to treat local infections. Fourteen formulas of tinidazole films were prepared by solvent evaporation method. Each film was composed of 10 mg tinidazole with different ratios and concentrations of a polymeric combination of polyvinyl alcohol/ polyvinyl pyrrolidone (PVA/PVP) or polyvinyl alcohol/ hydroxypropyl methylcellulose (PVA/HPMC) for formulas A1-A7 and B1-B7, respectively. The prepared films were evaluated for their physicochemical characteristics, content uniformity, swelling, mucoadhesive strength, mucoadhesive time, and drug release. All the prepared films were transparent, had a uniform thickness (0.1-0.15 mm), and exhibited sufficient flexibility with drug content uniformity. The mucoadhesive strength of films was in the range of 28 ± 0.2 to 75 ± 0.01 g. Films containing PVA/HPMC showed higher swelling and lower mucoadhesive strength than those containing PVA/PVP polymeric combination. The in vitro drug release study showed no significant differences (p > 0.05) among films containing PVA/PVP or PVA/HPMC polymeric combinations. Formulas A3 and B4 were considered as the optimal bioadhesive films containing 3% of PVA: PVP (4:1) and 4% of PVA: HPMC (2:1), respectively as they showed complete flexibility, acceptable mucoadhesive strength and time (43 ± 0.1, 45 ± 0.23 g and 30 ± 0.02, 34 ± 0.01 min, respectively) and prolonged drug release rate. In conclusion, films of formulas A3 and B4 possess the potential as a delivery system for tinidazole for the treatment of vaginal infections at the site of application.